From the Mouths of Babes: Lessons in Making a Joyful Noise unto the Lord - Deborah Ann Wong (Religions)
How do infants praise the Lord? While we cannot say definitively how this is so, exploring this idea—particularly in the context of intergenerational worship and formation—offers rich theological insights. Scripture declares, “Out of the mouth of babes and nursing infants, you have perfected praise” (Matthew 21:16; Psalm 8:2, NKJV), suggesting that (1) infants indeed praise God, and (2) their praise is perfected by Him. Rather than dismissing this as purely metaphorical, this article draws on St. Augustine’s concept of the jubilus, a song with no intelligible words, to explore how infants’ babbling might be seen as a form of praise and worship, and what we might learn from it if it is thus seen. The article concludes by demonstrating how this reflection on infants’ praise might challenge us to reevaluate and enrich our approaches to Contemporary Praise & Worship and intergenerational formation.